Dancing My Age: Emotions, Interactions, and Bodily Sensations - Heikkinen, Satu; Wilinska, Monika (Frontiers in Sports and Active Living, 2022)
While there is a growing body of research on the social aspects of older people’s dance, studies focusing on emotions are rare. In this study, we use an interactionist sociological perspective to examine the role of emotions in older social dancers’ experiences in Sweden. Through qualitative interviews with 29 active or previously active dancers, we found that their experiences of emotional energy and experiences of flow override concerns of age and aging. Age, however, did become significant as the age differences at dance events could bring forth feelings of alienation associated with feeling old. In addition, cultural and gendered norms of appropriate age differences between dancing partners produced shame and pride as well as feelings of being either old or young. Moreover, certain bodily experiences are interpreted in terms of age. Overall, the study contributes to the discussions of the complexity of subjective experiences of age by highlighting its emotional aspects through social partner dancing.